JUDICIAL INDEPENDENCE: HISTORICAL BACKGROUND AND MODERNITY - Shamshinurova Салтанат Муратовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The paper examines the main stages of the development of the judicial system in Kazakhstan. The author analyzes the historical and legal basisto constitute the judicial system. Particularly, author shows her view on the achievement of independence of the judiciary in terms of recent changes in this area. According to the author, the results of the judicial reforms testify establishment of the independent and autonomous judiciary in the country.